Ordinary community promoters... Estraordinary ones!!! - Llanos Zuloaga, Martha (2010)
The author shares her personal experiences in the Andes and the Himalayas as a tribute to the women community promoters of two continents, South America and South Asia. Profiles emerging from these Animators-Promoters express a number of special values in their personal and collective development, and that through their own work service such development increases and benefits others. Their training focuses on teaching and learning processes where we see that mostof the programs in both areas are oriented to the action-reflection-action based on a line of Freirian thought in full force and current expansion.